Penyuluhan Sprain Ankle pada Pelajar SMKN 6 Sukoharjo - Agus Widodo; Arif Pristianto; Aulia Nanda Viyanti; Nevada Bulandari Silaen; Zafaf Musyafa (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
The most common ankle injuries are ankle sprains. Ankle sprain is an overstretch of the lateral ligament complex due to inversion and plantar flexion forces which occur suddenly when the foot does not rest perfectly on the floor/ground, which generally occurs on an uneven floor/ground surface. An ankle sprain injury is usually caused when the surface of the ground or field is uneven so that the foot enters the uneven part of the ground and the foot position is not good and shock allows the support on the foot to be unbalanced. Therefore, physiotherapists play an important role in the community in promotive and preventive steps to overcome the problem of ankle sprains. Steps that can be taken are to provide education to the public about ankle sprains which includes understanding, signs and symptoms, prevention methods, main treatment, further treatment, and demonstration by respondents. The initial method for finding out the situation that occurs in the field is observation by interviewing teachers and related extracurricular students. The results of educational activities regarding ankle sprains are very useful for each individual's life. Knowledge about ankle sprains also increased from 5 to 24, this means students are starting to understand.